The association between organophosphate insecticides and blood pressure dysregulation: NHANES 2013-2014 - Frank Glover; Michael L. Eisenberg; Federico Belladelli; Francesco Del Giudice; Tony Chen; Evan Mulloy; W. Michael Caudle (BMC, 2022)
Abstract Background Organophosphate (OP) insecticides represent one of the largest classes of sprayed insecticides in the U.S., and their use has been associated with various adverse health outcomes, including disorders of blood pressure regulation such as hypertension (HTN). Methods In a study of 935 adults from the NHANES 2013-2014 cycle, we examined the relationship between systolic and diastolic blood pressure changes and urinary concentrations of three OP insecticides metabolites, including 3,5,6-trichloro-2-pyridinol (TCPy), oxypyrimidine, and para-nitrophenol. These metabolites correspond to the parent compounds chlorpyrifos, diazinon, and methyl parathion, respectively. Weighted, multivariable linear regression analysis while adjusting for potential confounders were used to model the relationship between OP metabolites and blood pressure. Weighted, multivariable logistic regression analysis was used to model the odds of HTN for quartile of metabolites. Results We observed significant, inverse association between TCPy on systolic blood pressure (β-estimate = -0.16, p < 0.001) and diastolic blood pressure (β-estimate = -0.15, p < 0.001). Analysis with para-nitrophenol revealed a significant, positive association with systolic blood pressure (β-estimate = 0.03, p = 0.02), and an inverse association with diastolic blood pressure (β-estimate = -0.09, p < 0.001). For oxypyrimidine, we observed significant, positive associations between systolic blood pressure (β-estimate = 0.58, p = 0.03) and diastolic blood pressure (β-estimate = 0.31, p < 0.001). Furthermore, we observed significant interactions between TCPy and ethnicity on systolic blood pressure (β-estimate = 1.46, p = 0.0036). Significant interaction terms were observed between oxypyrimidine and ethnicity (β-estimate = -1.73, p < 0.001), as well as oxypyrimidine and BMI (β-estimate = 1.51 p < 0.001) on systolic blood pressure, and between oxypyrimidine and age (β-estimate = 1.96, p = 0.02), race (β-estimate = -3.81 p = 0.004), and BMI on diastolic blood pressure (β-estimate = 0.72, p = 0.02). A significant interaction was observed between para-nitrophenol and BMI for systolic blood pressure (β-estimate = 0.43, p = 0.01), and between para-nitrophenol and ethnicity on diastolic blood pressure (β-estimate = 2.19, p = 0.006). Lastly, we observed a significant association between the odds of HTN and TCPy quartiles (OR = 0.65, 95% CI [0.43,0.99]). Conclusion Our findings support previous studies suggesting a role for organophosphate insecticides in the etiology of blood pressure dysregulation and HTN. Future studies are warranted to corroborate these findings, evaluate dose-response relationships between organophosphate insecticides and blood pressure, determine clinical significance, and elucidate biological mechanisms underlying this association.